Girl Math or Nonsense? – (De)valuation and (In)visibility of Women in Social Media Slang - Żak, Angelika (LingBaW. Linguistics Beyond and Within, 2025)
The study aims at presenting the phenomenon of the devaluation of women and their invisibility in youth-oriented language. The main focus of this research is social media and comments found in apps such as TikTok or X, which are some of the most popular social media platforms among teenagers. Language, just like a living organism, constantly changes to fit the needs of society, and since nowadays women are no longer only mothers and wives, the speech should reflect this phenomenon. The data is juxtaposed with women’s stereotypes found in the most popular proverbs. Therefore, upon examining the data, one is able to discover both changes and similarities between these two. The question posed in the article is whether slang still highlights the greatness of men and the weakness of women, just like the language used to present. Consequently, the main principle of the study is to establish whether any changes are happening with regard to the inclusivity of younger generations’ everyday speech. In other words, the objective of the article is to illustrate how patriarchal society affects slang, along with teenagers’ beliefs, as well as to present how the young generation breaks the cycle of stereotypical and sexist speech.